Pendampingan Pengelolaan Sampah Rumah Tangga Ibu-Ibu ‘Aisyiyah Cabang Puring Menggunakan Ember Bertumpuk - Ida Betanursanti; Galih Mahardika Munandar; Puji Warastri (Harmoni Sosial : Jurnal Pengabdian dan Solidaritas Masyarakat, 2024)
The community service program at Muhammadiyah Gombong University involves industrial engineering students and lecturers who assist the women of 'Aisyiyah Puring Branch in making liquid organic fertilizer from household waste. The goal is to improve family nutrition by providing training on using household waste to create liquid organic fertilizer using the stacked bucket method. The resulting fertilizer is used to nourish garden plants as a sustainable source of family nutrition. The mentoring process consists of four stages: preparation, education, practice, and maturation. As a result of the program, 60% of the participants have successfully produced fertilizer using the stacked bucket method. The best practices for making fertilizer are then shared with the surrounding community to encourage the habit of managing household waste effectively.